1988
DOI: 10.1037/0278-7393.14.2.266
|View full text |Cite
|
Sign up to set email alerts
|

Recognition failure of recallable unique names: Evidence for an empirical law of memory and learning.

Abstract: An experiment is described in which subjects (N = 106) studied unique names of famous individuals, such as ISAAC NEWTON and GEORGE WASHINGTON, and unique geographic names, such as TORONTO and STOCKHOLM, in the context of descriptive phrases. In a subsequent recognition test of the names in the absence of their study context, subjects failed to recognize many names that they could recall in the presence of the study context. These results (a) demonstrate the generality of the phenomenon of recognition failure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
74
0
1

Year Published

1990
1990
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(81 citation statements)
references
References 39 publications
6
74
0
1
Order By: Relevance
“…Evidence suggesting that Muter's (1984) results were due not to any representational properties of the names as assumed by generate-recognize theory but to overlap in the contextual information provided by the target and the cue was reported by Nilsson et al (1988), who showed that, when the contextual cues were less predictable from the targets, the relation between the recognition and recall of unique famous names was much as expected from Equation I.…”
Section: Recognition Of Recallable Music 633mentioning
confidence: 69%
See 1 more Smart Citation
“…Evidence suggesting that Muter's (1984) results were due not to any representational properties of the names as assumed by generate-recognize theory but to overlap in the contextual information provided by the target and the cue was reported by Nilsson et al (1988), who showed that, when the contextual cues were less predictable from the targets, the relation between the recognition and recall of unique famous names was much as expected from Equation I.…”
Section: Recognition Of Recallable Music 633mentioning
confidence: 69%
“…The claim that this relation between recognition and recall is lawful has been recently discussed by Gardiner (1988Gardiner ( , 1989, Jones and Gardiner (1990), Nilsson, Dinniwell, and Tulving (1987), and Nilsson, Law, and Tulving (1988). But the fullest review has been provided by Gardiner and Nilsson (1990), who state the law as follows:…”
mentioning
confidence: 99%
“…When data in the Nilsson-Gardiner (N-G) database were plotted in the Tulving-Wiseman (TW) graph space (i.e., with recognition success as the y-ordinate and probability of recognition as the x-abscissa), 92% of the data points conformed to the function. Therefore, some researchers Copyright 1998 Psychonomic Society, Inc. (Cohen, 1985;Jones, 1984;Nilsson, Law, & Tulving, 1988) have treated the TW function as an empirical law. Many other researchers (e.g., Arlemalm, 1996;Flexser & Tulving, 1978;Tulving, 1983) relied on the meta-analysis ofeither the TW or the N-G database to claim that recognition is the sole determinant ofrecognition success.…”
Section: P(rn Irc) = P(rn) + 5[p(rn) -P(rn)2] (1)mentioning
confidence: 99%
“…However, when the items were divided into two groups differing in memorability, a negative correlation appeared between recognition and guessing probability with the more memorable items, and a positive correlation appeared with the less memorable items. This suggests that response bias, rather than the memory the tasks are designed to test, is responsible for the normally reported lack of correlation between recognition and word completion.In a widely used experimental paradigm for studying memory, subjects are presented with a list of words and then are tested, first using a recognition task and then using a cued-recall or word-completion task (for a review, see Nilsson , Law, & Tulving, 1988). A measure of statistical association is then computed between the scores of the two tasks .…”
mentioning
confidence: 99%
“…In a widely used experimental paradigm for studying memory, subjects are presented with a list of words and then are tested, first using a recognition task and then using a cued-recall or word-completion task (for a review, see Nilsson , Law, & Tulving, 1988). A measure of statistical association is then computed between the scores of the two tasks .…”
mentioning
confidence: 99%